Preparation and characterisation of PVDF Sr₂.₅Yₒ.₅Fe₅O₁₂ particles composite - Mohd Saad, Mohd Hashim; Yahya, Noorhana; Shafie, Mohd Shamsul Ezzad; Ismail, Ismayadi; Bawa Waje, Samaila; Al-Habashi, Ramadan Masoud; Hashim, Mansor (Universiti Putra Malaysia Press, 2005)
Polyvinylidene fluoride (PVDF)-Sr2.5Y0.5Fe5O12 (SrYIG) particles film is investigated under scanning electron microscopy (SEM) technique for its surface morphology and physical compatibility studies. Films were prepared via powdersolution- gel-film phases with magnetic stirring at about 200 r.p.m and heating at about 90°C for 1 hour before the hot gel is poured into a dish for formation of thick film followed with atmospheric cooling for another 24 hours. Four samples were prepared with different SrYIG filler content of 0, 1, 5 and 10 wt%. The thick films were coated with gold for SEM analysis. SEM images were taken with JEOL 6400 scanning electron microscope and energy dispersive X-ray (EDX) analyses were also done with the same equipment. Magnetic characteristics were done on Agilent 4291B RF Impedance/Material Analyzer from 1MHz to 1.8GHz. SEM images showed that PVDF in cyclopentanone has surface that is relatively smooth. PVDF with magnetic fillers lost its smoothness and have granulated-like surface morphology instead. There is no clear evidence that the PVDF rejected the magnetic fillers though EDX analysis does not show existence of magnetic particles in the PVDF films. Magnetic properties of PVDF films were reduced when SrYIG fillers were introduced into the films.